The Research Review on Life Cycle Carbon Emissions in the Operational Process of Modular Buildings - Yupei Hu; Luyao Xiang; Kai Shang (Buildings)
Climate change has intensified scrutiny of the building sector, a major source of global greenhouse gas emissions. Modular construction, recognized for its environmental, economic, and social benefits, is increasingly regarded as a key strategy to achieve sustainability goals. This study systematically reviews literature from 2005 to 2025 on life cycle carbon emissions (CEs) during the operational phase of modular buildings, using the PRISMA model. A comprehensive search of Scopus, ScienceDirect, Web of Science (WoS), and relevant institutional databases yielded 1131 records, from which 34 studies were selected based on defined inclusion criteria. These studies span residential, commercial, and public buildings across Asia, North America, Europe, and Australia. Findings reveal that while carbon impacts during the construction phase of modular buildings are well documented, research on the operational phase remains limited due to data scarcity and methodological complexity. Since operational emissions typically exceed 60% of total life cycle emissions, and modular buildings offer advantages in airtightness, precision, and passive design integration, they hold significant potential for reducing emissions. This study calls for enhanced integration of technological innovation and policy incentives to support operational decarbonization and contribute to global carbon neutrality efforts.